Dilated cardiomyopathy due to novel LMNA mutation: a case report - Patel, Riddhi; Patel, Raj; Patel, Ekta; Patel, Mehul (Frontiers in Cardiovascular Medicine, 2024)
A case of a 44-year-old man presenting with a family history of LMNA mutation and cardiac symptoms (dizziness, weakness, palpitations, and shortness of breath) congruent with dilated cardiomyopathy. Genetic testing revealed a novel likely pathogenic mutation of the LMNA gene (c.513G>A, exon 2) not previously associated with dilated cardiomyopathy, and the patient underwent guideline direct treatment for dilated cardiomyopathy. In patients with LMNA mutations, VTA risk should be calculated to determine the need for prophylactic ICD placement.